Investigating the predictive role of vocabulary in written performance / Alice Su Chu Wong and Jocelyn Yee Vun Lee - Wong, Alice Su Chu; Lee, Jocelyn Yee Vun
Existing research recognises the critical role of vocabulary in the acquisition of a second (L2) or foreign language. In the context of L2 writing, it has been established that as vocabulary size increases, so does the ability to write more effective texts. The purpose of this study was to investigate the relationship between vocabulary size and ESL students’ written performance. The participants were 69 Malaysian university students whose writing skills were assessed as part of their English course requirement. Vocabulary size was measured using Laufer and Nation (1990) Vocabulary Level Test (VLT). Performance on the VLT was correlated with writing scores as a measure of written performance. Findings indicated that a majority of participants achieved a mastery level of the 2000-word test but had difficulty in the 3000-word and 5000-word level. Participants’ vocabulary size was also found to be strongly associated with their written performance. These results elucidate the importance of vocabulary knowledge in L2 writing. The pedagogical implication of the current work calls for the integration of vocabulary in writing classrooms.